(untitled) (Sociologisk Forskning, 1998)
Actions and outcomes. A discussion of two logics of co-action The article takes its point of departure from the three answers Other may give to Ego’s acts. Other may receive Ego’s act, and by that continue to accept Ego as an actor in the system. Or Other can demand an alternative act, which includes an acceptance of Ego as a continuous actor. Or, Other can reject the act of Ego, and by that also Ego as an actor. Ego is supposed to prefer Other’s reception of his act to a demand of an alternative and prefer the demand of an alternative to rejection. In systems of co-action these three answers can be constituted as two different logics of action outcome. The first logic can be looked upon as ”profit maximizing” , the second as ”cost minimizing” - even if these metaphors rather conceals the different social characteristics of the logics. A profit maximizing logic only accepts the reception of acts and equates demands for alternative acts with rejection of acts and actors. A cost minimizing logic avoids the rejection of acts and actors and equates by that the reception of acts with demands for alternative acts. The article concludes with some discussion of the analytical strength of these logics as theoretical instruments.